Julio López Gallardo (1941-2020) - Juan Carlos Moreno-Brid; Carlo Panico; Martín Puchet (PSL Quarterly Review, 2020)
This obituary recalls the personal and intellectual trajectory of Julio López Gallardo, who recently passed away. A friend of the authors and this Review, Julio contributed widely to the literature on the development of Latin American countries, to Kaleckian models, and to structuralism. His main contributions concern the effective demand in the semi-industrialized economies, the different roles of fiscal and trade deficits in economic growth, and the structural role of the distribution of income on the development process.
Keywords: B32; E11; O11; 330; Julio López; Structuralism; Kalecki